Understanding the present and preparing for the future: Exploring the needs of diagnostic and elective genomic medicine patients. Issue 2 (9th April 2019) - East, Kelly M.; Cochran, Meagan; Kelley, Whitley V.; Greve, Veronica; Emmerson, Kristina; Raines, Grace; Cochran, Jesse Nicholas; Hott, Adam M.; Bick, David
Abstract: Advances in genomic knowledge and technology have increased the use of comprehensive clinical sequencing tests. Genome sequencing has established utility for diagnosing patients with rare, undiagnosed diseases as well as interest in an elective context, without a clinical indication for testing. The Smith Family Clinic for Genomic Medicine, LLC in Huntsville, AL is a private practice genomic medicine clinic caring for both diagnostic (79%) and elective (21%) patients. Diagnostic and elective patients are seen on a clinical basis and receive standard care. Genome sequencing is provided on a self‐pay basis, with assistance available for diagnostic patients who have financial need. Here, we describe demographics and motivations of the distinct patient populations and our experiences engaging patients in online education. Diagnostic patients were motivated by the possibility of receiving an explanation for symptoms (96%) while elective patients were motivated by the chance to learn about future disease risk (57%). Elective patients were less likely to engage with online education, with only 28% reading all assigned topics compared to 54% of diagnostic patients. Understanding the needs, interests, and barriers unique to diagnostic and elective patients is critical to inform individualized and scalable best practices in patient education and engagement.